2014
DOI: 10.1063/1.4861587
|View full text |Cite
|
Sign up to set email alerts
|

The nucleation process and the roles of structure and density fluctuations in supercooled liquid Fe

Abstract: We observed homogeneous nucleation process of supercooled liquid Fe by molecular dynamics simulations. Using bond-orientational order parameters together with Voronoi polyhedron method, we characterized local structure, calculated the volume of Voronoi polyhedra of atoms and identified the structure and density fluctuations. We monitored the formation of nucleus and analyzed its inner structure. The birth and growth of the pre-nucleus and nucleus are accompanied with aggregating and disaggregating processes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…local density) and orientational (bond orientational ordering) order. Recently, the role of density fluctuation and development of bond orientational ordering on the crystallization process is investigated for bodycenteredcubic (bcc) refractory metals Nb [4] and V [5] using ab initio molecular dynamics, and Fe [6] using classical molecular dynamics; and concluded that the early stage of nucleation is mainly driven by the fluctuation of bond orientational ordering rather than density fluctuation which is consistent with the proposed nucleation scenario by Tanaka and coworkers for colloidal systems [7][8][9].…”
Section: Introductionsupporting
confidence: 71%
“…local density) and orientational (bond orientational ordering) order. Recently, the role of density fluctuation and development of bond orientational ordering on the crystallization process is investigated for bodycenteredcubic (bcc) refractory metals Nb [4] and V [5] using ab initio molecular dynamics, and Fe [6] using classical molecular dynamics; and concluded that the early stage of nucleation is mainly driven by the fluctuation of bond orientational ordering rather than density fluctuation which is consistent with the proposed nucleation scenario by Tanaka and coworkers for colloidal systems [7][8][9].…”
Section: Introductionsupporting
confidence: 71%
“…One can see that an initial nucleation occurs at T n = 0.38T cal m and the maximum I max related to a critical temperature of nucleation [24] emerges at T n = 0.45T cal m , but both of which are far away from the thermodynamic under-cooling T m = 0.42T cal m . These results clearly indicate nucleation as a dynamic behavior cannot be directly inferred from an abrupt change in thermodynamic parameters such as E (T), V (T) and q (T) [56]. Nevertheless, from a statistical point of view, a good agreement between thermodynamic events and dynamic behaviors can be observed.…”
Section: T-dependence Of Size and Quantitymentioning
confidence: 85%
“…Voronoi polyhedral analyses is a geometrical spatial method and, can identify the unknown structures and give some statistics information about individual atoms such as the atomic coordination number and 3-D space shared by the central atom and all its neighbors. The Voronoi polyhedron method has been proven to be effective for the analyses of local atomic environment 31 and the volume of cluster 32 in liquids and glasses. The Voronoi index is expressed as < n 1 ,n 2 ,n 3 ,n 4 >, where n i denotes the number of i -edged faces of the Voronoi polyhedrons 33 34 35 .…”
Section: Resultsmentioning
confidence: 99%